2019
DOI: 10.1163/15685381-18000008
|View full text |Cite
|
Sign up to set email alerts
|

Space fit for a king: spatial ecology of king cobras (Ophiophagus hannah) in Sakaerat Biosphere Reserve, Northeastern Thailand

Abstract: A species’ spatial ecology has direct implications for that species’ conservation. Far-ranging species may be more difficult to conserve because their movements increase their chances of encountering humans. The movements can take them out of protected areas, which is especially risky for species that are routinely persecuted. The king cobra (Ophiophagus hannah), a large venomous elapid, is subject to anthropogenic pressures, such as persecution and habitat loss. Here we present results from a study using radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…The transitional zone also contains 159 villages and a four-lane highway that 74 connects Nakhon Ratchasima to Bangkok. Further descriptions of the study site can be found in Silva 75 et al (2018) and Marshall et al (2018Marshall et al ( , 2019. 76…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transitional zone also contains 159 villages and a four-lane highway that 74 connects Nakhon Ratchasima to Bangkok. Further descriptions of the study site can be found in Silva 75 et al (2018) and Marshall et al (2018Marshall et al ( , 2019. 76…”
mentioning
confidence: 99%
“…The capture and implantation methods, alongside King Cobra measurements, have been previously 77 described in Marshall et al (2018Marshall et al ( , 2019. We tracked individuals four times a day, with approximately 78 four hours between tracks from 2014-03-22 to 2018-07-28 (06:30, 11:00, 16:00, 20:00; the distribution 79 of time lags between tracking is available in Supplementary Figure 1).…”
mentioning
confidence: 99%
“…Aquatic environments and the vegetation that typically grows on the edges of ponds and irrigation canals could also serve as suitable refuge in an area highly modified by human settlements, roads, and agricultural practices. Furthermore, irrigation canals could also serve as movement corridors for Burmese pythons as seen with King Cobras that often travel along irrigational canals while in the agricultural land within our study site (Marshall 2020b;Marshall et al, 2019). The use of connected systems of aquatic agriculture in their native range (this study site, rice paddies and irrigation canals, Thailand) may help explain their success in their invasive range (natural everglade wetlands, Florida, USA) that is similarly characterized by interconnected wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Movement is often conceptualized then presented as a home range, defined as the area animals move through during “normal” activities, including resource acquisition and reproduction [ 3 , 4 ]. While the utility of the home range concept has been questioned in recent years [ 5 , 6 ], its estimation continues to have a wide range of applications, such as identifying behavioural adaptations to predictable environmental features [ 7 ] or inferring habitat use [ 8 11 ]. It is clear that different biological questions have different appropriate estimators [ 12 ], but reptile spatial ecology studies evaluate not only long-term area requirements, but also movement behaviour and space-use regardless of the assumptions and applicability of each estimation method.…”
Section: Introductionmentioning
confidence: 99%